COMPARISON OF HEALTH INSURANCE PREMIUMS FOR BPJS PARTICIPANTS AND PRIVATE HEALTH INSURANCE - zikra, safaratul; Nurdin, Ambia (Jurusan Kesehatan Lingkungan, Poltekkes Kemenkes Aceh, 2023)
BPJS is a legal entity whose function is to organize a health insurance program for all Indonesian people, including foreigners who work for a minimum of 6 months in Indonesia. This health insurance is in the form of health protection so that participants receive health care benefits and protection in meeting basic health needs that are given to everyone who has paid contributions or whose contributions have been paid by the government. This research is more focused on comparative research, namely comparative research, in this case comparing the results of calculating business entity BPJS insurance premiums with private health insurance premiums, where the results will be derived to see the advantages and disadvantages of each. The results of a comparison of the calculation of BPJS health insurance premiums and private health insurance results in BPJS health insurance premiums being much cheaper than private health insurance premiums. With such a premium calculation, it will explain more about the advantages and disadvantages between business entity BPJS health insurance and private health insurance.